Requirements for Applying Knowledge Management to Improve Electronic Management in Educational Institutions in Light of Digital Transformation: An Analytical Study (The International Journal of Educational Sciences and Arts, 2024)
The study aimed to reveal the requirements for applying knowledge management to improve electronic management in educational institutions in light of digital transformation. The study followed the deductive approach and the descriptive analytical approach by referring to previous studies and deriving concepts related to knowledge management applications in the context of educational institutions, and analyzing statistical reports for the Information Technology Department at the Ministry of Education. The study concluded that to apply knowledge management (discovery, generation, sharing, implementation and sustainability) to improve electronic management in educational institutions: Organizational requirements: include strategic planning for the transformation process towards the digital world, leadership and administrative support, and the commitment of senior management to support... The electronic administration project and the flexible organizational structure were adopted, and legislative frameworks were established and updated in accordance with developments, and the material and technical requirements: such as infrastructure, the availability of programs and applications, the design of database system software such as “Oracle”, the presence of communication networks, service centers, and the availability of electronic means necessary to benefit from the services provided by the administration. Electronic and human requirements: educating and training employees to develop the skills of applications of knowledge management processes in electronic administration. Attracting the best qualified individuals in the fields of information systems and software, creating effective systems to retain, develop and motivate individuals, and financial requirements: providing financial support and security requirements: represented in information security, ensuring and protecting the database, and providing privacy and confidentiality to protect the information, and recommended the importance of achieving the requirements by relying on practical methods. Which requires the availability of leading expertise and specializations for digital transformation, and the use of knowledge management to manage the use and activation of technologies to provide opportunities for digital transformation.
Keywords: Knowledge Management; Knowledge Management Requirements; Electronic Management; Educational Institutions; Digital Transformation